2009
DOI: 10.1007/s10162-009-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Contralateral Acoustic Stimulation on Spontaneous Otoacoustic Emissions

Abstract: Evoked otoacoustic emissions are often used to study the medial olivocochlear (MOC) efferents in humans. There has been concern that the emission-evoking stimulus may itself elicit efferent activity and alter the evoked otoacoustic emission. Spontaneous otoacoustic emissions (SOAEs) are hence advantageous as no external stimulation is necessary to record the response in the test ear. Contralateral acoustic stimulation (CAS) has been shown to suppress SOAE level and elevate SOAE frequency, but the time course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 68 publications
6
50
0
Order By: Relevance
“…For clarity, changes in SOAE frequency and level with CAS are shown in panel C. Ear canal spectra in quiet and CAS for one subject are also shown in panel A, demonstrating the typical CAS-mediated reduction in SOAE amplitude and upward shift in SOAE frequency. These changes were representative of the effects observed on the total population of SOAEs from which the selected SOAEs were taken and are consistent with previous reports of the effects of CAS on SOAEs Harrison and Burns 1993;Zhao and Dhar 2010, 2011.…”
Section: Soae-specific Measurementssupporting
confidence: 89%
See 3 more Smart Citations
“…For clarity, changes in SOAE frequency and level with CAS are shown in panel C. Ear canal spectra in quiet and CAS for one subject are also shown in panel A, demonstrating the typical CAS-mediated reduction in SOAE amplitude and upward shift in SOAE frequency. These changes were representative of the effects observed on the total population of SOAEs from which the selected SOAEs were taken and are consistent with previous reports of the effects of CAS on SOAEs Harrison and Burns 1993;Zhao and Dhar 2010, 2011.…”
Section: Soae-specific Measurementssupporting
confidence: 89%
“…This shift was anticipated based on previously observed effects of CAS on SOAEs Harrison and Burns 1993;Zhao and Dhar 2010, 2011 and the close frequency correspondence between threshold minima and SOAEs (e.g., Wilson 1980;Schloth 1983;Zwicker and Schloth 1984). We confirmed that threshold minima occurred very near in frequency to each selected SOAE, with frequency discrepancies typically less than a few Hz (or 0.1 %), both in quiet and with CAS.…”
Section: Frequency Shifts In Threshold Minima and Soaessupporting
confidence: 87%
See 2 more Smart Citations
“…This finding disagrees with studies that indicate that children with auditory processing disorders have a decreased level or absence of suppression of otoacoustic emissions (14)(15)18) . Moreover, other findings assume that the figure-ground ability is directly related to the MOCS reflex, that is, the higher this ability, the greater the suppression of OAE (28,29) . The figure-ground ability is the one that seems to be more affected in subjects with phonological disorders, which disagrees with previous findings (16) .…”
Section: Discussionmentioning
confidence: 99%